The citotoxicity of calcium hydroxide intracanal dressing by MTT assay - Nanik Zubaidah (Dental Journal (Majalah Kedokteran Gigi), 2007)
Calcium hydroxide had been used as the intracanal dressing in endodontic treatment due to its high alkaline and high antimicrobial capacity. It also be able to dissolve the necrotic tissue, prevent the root resorbtion and regenerate a new hard tissue. The aim of this study is to identify the concentration of calcium hydroxide that has the lowest citotoxicity. There are 5 groups, each group had 8 samples with different concentration of calcium hydroxide. Group I: 50%, Group II: 55%, Group III: 60%, Group IV: 65% and Group V: 70%. The citotoxicity test by using enzymatic assay of MTT [3-(4.5- dimethylthiazol-2yl) ]-2.5 diphenyl tetrazolium bromide, against fibroblast cell (BHK-21). The result of susceptibility test was showed by the citotoxicity detection of the survive cell of fibroblast that was measured spectrophotometrically using 595 nm beam. The data was analyzed using One-Way ANOVA test with significant difference α = 0.05 and subsequently LSD test. The result showed that in concentration 50%, 55%, 60%, 65%, and 70% calcium hydroxide had low toxicity, but calcium hydroxide 60%, had the lowest toxicity.